Magnetic signatures of plasma interaction and induction at Callisto: The Galileo C21, C22, C23, and C30 flybys. Issue 7 (17th July 2017) - Liuzzo, Lucas; Simon, Sven; Feyerabend, Moritz; Motschmann, Uwe
Abstract: We apply a combination of analytical modeling, hybrid simulations, and data analysis techniques to provide a comprehensive study of magnetometer data from four Galileo flybys of Callisto (C21, C22, C23, and C30) that have never been discussed in the literature before. Callisto's distance to the center of Jupiter's magnetospheric current sheet varied considerably from flyby to flyby. Therefore, the relative strength of the magnetic field perturbations due to Callisto's plasma interaction with Jupiter's magnetosphere and induction within Callisto's subsurface ocean drastically changed as well. During C21, a strong magnetic field perturbation along the corotation direction was detected in Callisto's geometric plasma shadow. This enhancement can be explained with Callisto's steady state plasma interaction only, if the upstream flow possessed a nonnegligible component away from Jupiter. During C22, Galileo only grazed Callisto's Alfvén wings which were elevated out of the flyby plane due to the ambient magnetospheric field orientation. During C23, the combination of an inclined flyby trajectory and finite gyroradius effects caused Callisto's observed Alfvén wings to be slightly asymmetric between both hemispheres. During C30, a discontinuity with a surface normal pointed toward Jupiter was detected within Callisto's geometric plasma shadow, similar to the earlier C10 flyby. Due to strong plasma interaction and an unfavorable flyby geometry (C21), a large closest approach altitude (C22), or weak inducing field (C23 and C30), no discernible induction signatures were observed during these four flybys. Based on data from all available Galileo flybys, we determine requirements on future flyby geometries that must be satisfied for an identification of Callisto's subsurface ocean in magnetometer data. Key Points: First comprehensive study of magnetic field data from all Galileo flybys of Callisto Induction signal from Callisto's subsurface ocean is observable only under very specific plasma conditions We provide encounter geometries for future Callisto flybys to detect magnetic signature of ocean